Challenging Problems and Solutions in Intelligent Systems - Trė, Guy de; Grzegorzewski, Przemysław; Kacprzyk, Janusz; Owsiński, Jan W.; Penczek, Wojciech; Zadrożny, Sławomir (Studies in Computational Intelligence, 2016)
This volume presents recent research, challenging problems and solutions in Intelligent Systems- covering the following disciplines: artificial and computational intelligence, fuzzy logic and other non-classic logics, intelligent database systems, information retrieval, information fusion, intelligent search (engines), data mining, cluster analysis, unsupervised learning, machine learning, intelligent data analysis, (group) decision support systems, intelligent agents and multi-agent systems, knowledge-based systems, imprecision and uncertainty handling, electronic commerce, distributed systems, etc. The book defines a common ground for sometimes seemingly disparate problems and addresses them by using the paradigm of broadly perceived intelligent systems. It presents a broad panorama of a multitude of theoretical and practical problems which have been successfully dealt with using the paradigm of intelligent computing.